A new species and new record of Reticulolaelaps Costa (Acari: Laelapidae) from Iran - Nemati, Alireza; Joharchi, Omid; Babaeian, Esmaeil; Gwiazdowicz, Dariusz J. (Zootaxa, 2013)
We describe a new species of mite from Iran—Reticulolaelaps hallidayi Joharchi, Nemati & Babaeian sp. nov. (Acari: Laelapidae). The new species was collected in a nest of Tapinoma sp. (Hymnoptera: Formicidae) in Taleghan city, Alborz Province and in soil in Khuzestan province in southwestern Iran. Reticulolaelaps faini is reported for the first time from Iran. The genus Reticulolaelaps is redescribed, and Reticulolaelaps lativentris Karg is transferred to Pseudoparasitus Oudemans.